Application of knowledge, belief and action model in ICU stress injury nursing training: A pre-post controlled study - Shaozhen Chen; Jinxia Li; Mian Zeng (Journal of the Pakistan Medical Association, 2025)
Objective: To explore the application effect of the knowledge, belief and action model in intensive care unit stress injury nursing training. Method:The pre-post study was conducted at the First Affiliated Hospital of Sun Yat-sen University, China, from January 1, 2020, to December 31, 2022, and comprised nurses associated with intensive care unit. The stress-related knowledge of the nurses was assessed using a questionnaire adapted from literature in the light of the knowledge, belief and action model. Data was collected at baseline, followed by stress injury training for the nurses, including theoretical and practical sessions. The same questionnaire was used to collect post-training data. Data was analysed using SPSS 22. Results: Of the 110 nurses, 98(89%) were females and 12(11%) were males. The overall mean age was 23.59±2.66 years (range: 19-26 years). Of the total, 86(78.2%) were without licence, 20(18.2%) were nurses, and 4(3.6%) were senior nurses. Compared to baseline, stress injury knowledge, stress injury attitude and stress injury practice behaviour scores were significantly higher post-training (p<0.05). Compared to baseline, the dressing change scores of the nurses post-training were significantly improved (p<0.05). Conclusion: The application of the knowledge, belief and action model improved the ability of intensive care unit nurses to recognise stressful injuries, and enabled them to correctly assess the patients with high risk of stressful injuries and pressure injuries related to medical devices. Keywords: Stress injury, Nursing, Knowledge, belief and action model, training, intensive care unit.